2020
DOI: 10.1002/jia2.25610
|View full text |Cite
|
Sign up to set email alerts
|

Early access to antiretroviral therapy versus standard of care among HIV‐positive participants in Eswatini in the public health sector: the MaxART stepped‐wedge randomized controlled trial

Abstract: Introduction: The WHO recommends antiretroviral treatment (ART) for all HIV-positive patients regardless of CD4 count or disease stage, referred to as "Early Access to ART for All" (EAAA). The health systems effects of EAAA implementation are unknown. This trial was implemented in a government-managed public health system with the aim to examine the "real world" impact of EAAA on care retention and viral suppression. Methods: In this stepped-wedge randomized controlled trial, 14 public sector health facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…These findings are reassuring given the limited existing literature on the impact of UTT on client adherence and retention. The primary study analysis showed improvements in client retention in care upon UTT implementation compared with standard of care [3]. The primary study analysis also determined that factors including lack of social support, care delivery, drug side effects and employment issues contributed to loss to follow‐up [4], and there were no significant differences in patient satisfaction between UTT and standard of care arms [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are reassuring given the limited existing literature on the impact of UTT on client adherence and retention. The primary study analysis showed improvements in client retention in care upon UTT implementation compared with standard of care [3]. The primary study analysis also determined that factors including lack of social support, care delivery, drug side effects and employment issues contributed to loss to follow‐up [4], and there were no significant differences in patient satisfaction between UTT and standard of care arms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Details on the MaxART Early Access to ART for All implementation study have been described previously [3]. In brief, this 3‐year stepped‐wedge randomized trial had open enrolment for all ART‐naïve adults aged ≥ 18 years across 14 government‐managed health clinics in Eswatini's Hhohho Region from September 2014 to August 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the MaxART Early Access to ART for All implementation study have been published previously [9–12]. In brief, this 3‐year stepped‐wedge randomized trial had open enrolment for all adults ≥ 18 years old across 14 public sector‐managed health clinics in Eswatini's Hhohho Region from September 2014 to August 2017.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if inflammation were to be confirmed as an important mediator of the obesity–lethal prostate cancer relationship, new approaches to the prevention, prediction, and the treatment of prostate cancer would likely emerge [ 3 ]. As another example, the anti-retroviral intervention referred to as “Early Access to ART for All” (EAAA) was found effective to improve the retention in care compared to the standard of care among HIV-positive patients in the MaxART study [ 4 ]. If we can identify an important mediator in the pathway between the intervention and HIV care retention, new strategies targeting the mediator may be developed to further improve outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we describe our Monte Carlo simulation study that investigates the performance of the point and interval estimators for NIE and MP, and report our findings. To illustrate the product method, we study how much the effect of an EAAA intervention on 12-month retention is mediated by the 6-month visit adherence in the MaxART study [ 4 ]. Finally, we offer a brief discussion.…”
Section: Introductionmentioning
confidence: 99%